(untitled) (Journal of Academic Research, 2026)
This study investigates the impact of using artificial intelligence (AI) technologies on the efficiency of learning English for Specific Purposes (ESP) among graduate students at the Libyan Academy for Graduate Studies – Derna Branch. The study employed a descriptive quantitative analytical approach and was conducted on a sample of 65 students from various scientific and humanities disciplines. A structured questionnaire was used as the primary data collection tool. The results revealed a significant positive correlation between the use of AI technologies and the improvement of ESP learning efficiency. Interactive chatbots (Chatbots) were identified as the most influential tools in enhancing linguistic fluency and simulating authentic communicative situations. Additionally, the vocabulary and academic writing dimension received the highest level of agreement regarding the benefits of A. Regarding individual differences, the study found that female students used AI technologies more extensively than their male counterparts. Conversely, adaptive systems and automated assessment tools showed no significant effect on writing skills. As for challenges, technical obstacles and privacy concerns were not considered major barriers to AI adoption among students. Based on these findings, the study recommends integrating chatbots into curricula, developing adaptive systems to strengthen writing skills, and emphasizing the instructor’s role as a guide to ensure that AI tools are utilized as supportive aids rather than substitutes in the educational process.